Royal capitalism : wealth, class, and monarchy in Thailand - Puangchon Unchanam (Madison, Wisconsin : The University of Wisconsin Press, 2020)
"Classical theorists once predicted that monarchy must eventually give way to capitalism. But is monarchy really dead--an archaic institution from the feudal past? In Royal Capitalism: The Monarchy, Wealth, and Social Classes in Thailand, Puangchon Unchanam examines one particularly successful monarchy: that of Thailand's King Bhumibol Adulyadej or Rama IX, whose seven-decade reign not only survived but thrived amid the country's transition to industrial capitalism. Indeed, the Thai crown's active role in national politics, the market economy, and popular culture has made it not only the dominant institution in the kingdom, but also the wealthiest monarchy in the world today. Tracing Rama IX's reign (1946-2016), Puangchon shows how the Thai crown was transformed into a 'bourgeois monarchy,' distinctive in several key ways. Rather than representing only royal and religious values, the monarchy rebranded itself by embracing the traditional middle-class ethic of hard work, frugality, and self-sufficiency. Rather than only relying upon coercion, the crown sought political legitimacy. And rather than simply controlling national assets, the crown became the country's major broker, connecting business elites, patronizing their industries, and partnering with giant corporations. Thanks to these distinctive features that it has recently embodied, the Thai monarchy enjoys hegemonic status in the capitalist state, preeminent status in the market, and popular support from the urban bourgeoisie"--
Introduction: The king is (not) dead, long live capitalism! -- 1 The genesis of the bourgeois monarchy -- 2 The rise and triumph of the bourgeois crown -- 3 The king and (bourgeois) eyes -- 4 The crown versus the crowd -- 5 All hail the king.
Includes bibliographical references and index.
Keywords: Bhumibol Adulyadej, -- King of Thailand, -- 1927-2016.; Monarchy -- Thailand; Capitalism -- Thailand